Funny money [videorecording (DVD)] - Greif, Leslie; Greif, Leslie; Greif, Leslie; Chase, Chevy; Miller, Penelope Ann; Assante, Armand, 1949-; Loggia, Robert; Cooney, Ray (Distributed by Starz Home Entertainment, 2007)
Henry Perkins, a mild-mannered accountant, accidentally trades briefcases with another man to find out that there's a million dollars inside. Henry tells his unsuspecting wife of their new-found fortune, but she doesn't embrace it as well as he does. Soon they're joined by their best friends, a cop on the take, a cop on the hunt, and the dreaded Mr. Big who has come to claim his money.